Women's Perceptions and Feelings about Loss of Their Sexual Desire A Qualitative Study in Iran - Akhavan Akbari, Pouran PhD Candidate (International journal of community based nursing and midwifery, 2018)
BACKGROUND: Reduced sexual desire leaves serious impacts on women's life. The current study aims to investigate the perceptions and concerns of Iranian women of reproductive age with female sexual interest and arousal disorder (FSIAD)